Hibiscus sabdariffa extract lowers blood pressure and improves endothelial function. Issue 6 (24th February 2014) - Joven, Jorge; March, Isabel; Espinel, Eugenia; Fernández‐Arroyo, Salvador; Rodríguez‐Gallego, Esther; Aragonès, Gerard; Beltrán‐Debón, Raúl; Alonso‐Villaverde, Carlos; Rios, Lidia; Martin‐Paredero, Vicente; Menendez, Javier A.; Micol, Vicente; et al.
<x xml:space="preserve">Abstract</x> Polyphenols from Hibiscus sabdariffa calices were administered to patients with metabolic syndrome (125 mg/kg/day for 4 wk, n = 31) and spontaneously hypertensive rats (125 or 60 mg/kg in a single dose or daily for 1 wk, n = 8 for each experimental group). The H. sabdariffa extract improved metabolism, displayed potent anti‐inflammatory and antioxidant activities, and significantly reduced blood pressure in both humans and rats. Diuresis and inhibition of the angiotensin I‐converting enzyme were found to be less important mechanisms than those related to the antioxidant, anti‐inflammatory, and endothelium‐dependent effects to explain the beneficial actions. Notably, polyphenols induced a favorable endothelial response that should be considered in the management of metabolic cardiovascular risks.